Edukasi Interaktif sebagai Upaya Meningkatkan Pengetahuan Kesehatan Mental Remaja - Isnaeni Anggun Sari; Lia Dwi Jayanti (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
Mental health is a crucial issue that needs attention among adolescents. Adolescents low level of mental health knowledge can impact their ability to recognize their current psychological conditions and how to obtain appropriate psychological assistance. The purpose of this community service activity is to increase the knowledge of Junior High School students regarding mental health through interactive educational workshops. The main focus of this community service activity is to increase mental health knowledge related to the characteristics of mental health, how to maintain mental health and overcome problems, and recognize myths and facts about mental health. The implementation method used a one-group pre-test and post-test design to evaluate the impact of education. The activity subjects were 30 junior high school students. The evaluation instrument was a mental health knowledge questionnaire administered before (pre-test) and after (post-test) the educational activity. The pre-test results showed that most participants had a limited level of mental health knowledge. After receiving mental health education, the post-test results showed an increase in knowledge scores in most participants. The research data were analyzed using the Wilcoxon Signed Rank Test. The analysis results showed a significant difference between knowledge scores before and after the educational activity (p < 0.05), indicating that mental health education was effective in improving the knowledge of junior high school students. This community service activity is expected to be a promotive and preventive effort in improving adolescent mental health literacy in the school environment.